Remote preconditioning improves maximal performance in highly trained athletes - Jean St. Michel, E.; Manlhiot, C.; Li, J.; Tropak, M.; Michelsen, M. M.; Schmidt, M. R.; McCrindle, B. W.; Wells, G. D.; Redington, A. N. (Medicine & Science in Sports & Exercise, 2011)
Background: Remote ischemic preconditioning (RIPC) induced by transient limb ischemia releases a dialysable circulating protective factor that reduces ischemia-reperfusion injury. Exercise performance in highly trained athletes is limited by tissue hypoxemia and acidosis, which may therefore represent a type of ischemia-reperfusion stress modifiable by RIPC. Methods and Results: National-level swimmers, 13-27 yr, were randomized to RIPC (four cycles of 5-min arm schemia/5-min reperfusion) or a low-pressure control procedure, with crossover. In study 1, subjects (n = 16) performed two incremental submaximal swimming tests with measurement of swimming velocity, blood lactate, and HR. For study 2, subjects (n = 18) performed two maximal competitive swims (time trials). To examine possible mechanisms, blood samples taken before and after RIPC were dialysed and used to perfuse mouse hearts (n = 10) in a Langendorff preparation. Infarct sizes were compared with dialysate obtained from nonathletic controls. RIPC released a protective factor into the bloodstream, which reduced infarct size in mice (P < 0.05 for controls and swimmers). There was no statistically significant difference between the effect of RIPC and the low-pressure control protocol on submaximal exercise performance. However, RIPC was associated with a mean improvement of maximal swim time for 100 m of 0.7 s (P = 0.04), an improvement in swim time relative to personal best time (-1.1%, P = 0.02), and a significant improvement in average International Swimming Federation points (+22 points, P = 0.01). Conclusions: RIPC improves maximal performance in highly trained swimmers. This simple technique may be applicable to other sports and, more importantly, to other clinical syndromes in which exercise tolerance is limited by tissue hypoxemia or ischemia.